La alquimia de una dominación y la posibilidad de su transformación : Educación y política en P. Bourdieu - Gambarotta, Emiliano Matías (2016)
This paper addresses the perspective of Pierre Bourdieu conceived it as an extensive research on the social domination. In this context, the article focuses on his research concerning the education system so as to identify the different mechanisms by which this system contributes to the reproduction of the established relations of domination. Based on these aspects, the criticisms are questioned Henry Giroux makes Bourdieu's perspective, from its ?resistance theory?. Finally, we investigate the ways in which it may suspend such mechanisms were and, with them, the relations of domination.
Este trabalho aborda a perspectiva de Pierre Bourdieu concebendo-a como uma vasta pesquisa sobre a dominaçao social. Neste contexto, o artigo concentra-se nas suas pesquisas referentes ao sistema de ensino para assim identificar os diferentes mecanismos através dos quais esse sistema contribui com a reproduçao das relaçoes de dominaçao estabelecidas. Com base nestes aspectos, sao questionadas as criticas que Henry Giroux faz à perspectiva de Bourdieu, a partir da sua "teoria da resistência". Finalmente, investigamos as maneiras pelas quais poder-se-iam suspender tais mecanismos e, com eles, as relaçoes de dominaçao.
Documento incorporado en 2019 en el marco del "Programa de becas de experiencia laboral" de la Biblioteca Profesor Guillermo Obiols para estudiantes de Bibliotecología, a partir de un procedimiento técnico de captura de datos desarrollado por el personal del IdIHCS.
Keywords: Education System; Symbolic alchemy; School nobility; Sistema de ensino; Alquimia simbólica; Nobreza escolar; Bourdieu, Pierre; Educación; Sistemas educativos; Política; Control social